Analisis Strategi Customer Bonding Untuk Membangun Loyalitas Pelanggan Pada Labella Hijab Store Lamongan - Madar, Suyitno; Wahyuningsih, Yulie; Wahyuku Ningtiyas, Putri (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Research aim : This study aims to describe the implementation of customer bonding strategies through digital marketing in building customer loyalty at Labella Hijab Store Sendangagung Paciran Lamongan. Design/Methode/Approach : This study used a qualitative research method with a descriptive qualitative approach. Data collection techniques through observation, interviews and documentation. Research Finding : The results showed that Labella Hijab Store used five levels of customer bonding: awareness bonding, identity bonding, relationship bonding, community bonding and advocacy bonding. Labella Hijab's type of customer loyalty is at the highest level, namely: liking the brand and committed. The results of this study also show the importance of Labella Hijab Store in maintaining and improving customer bonding strategies, especially through optimizing advocacy bonding by stimulating the birth of indirect marketers on an ongoing basis, in an effort to bind and strengthen customer trust so that loyalty increases. Theoretical contribution/Originality : This research provides evidence that implementing a customer bonding strategy accompanied by digital marketing via the internet with various platforms such as web, social media and e-commerce is very effective in maintaining hijab sales.in binding and fostering a sense of customer trust. Practitionel/Policy implication : The strategy of customer bonds and digital marketing has a role in increasing sales, binding and growing trust in consumers, so management must use the two combined strategies in order to be able to buildmassive customer loyalty. Research limitation : This research only focuses on customer bonding factors and digital marketing through social media only.